Arabic Digital Comic Media on Students' Vocabulary Mastery and Reading Ability - Muhammad Risal Rhomadan; Anik Ghufron; Euis Nurmiati; Andi Rabuandika (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Lack of learning media has an impact on low student learning outcomes. This study aims to produce an effective website-based Arabic digital comic media to improve vocabulary mastery and reading skills. This research and development (RnD) study uses the Borg and Gall development research model, which refers to 10 stages. The research subjects are material experts and media experts. The trial subjects consisted of 96 grade IV elementary school students. Data collection is done through interviews, observations, questionnaires, and tests. The techniques used to analyze the data are qualitative, quantitative, descriptive analysis, and inferential statistics. The study results showed that digital comic media obtained a score of 99 from material experts with very feasible criteria. The website-based Arabic digital comic media also obtained a score of 120 from media experts with feasible criteria. Digital comic media meets the criteria of practicality based on initial and foremost field trials. The digital comic media produced has met the criteria for effectively improving grade IV elementary school students' vocabulary mastery and reading skills. This is based on the N-gain score, which shows that the value of vocabulary mastery and reading skills in the experimental class is higher than in the control group. The results of the MANOVA test show that digital comic media can improve the mastery of vocabulary and the ability to read Arabic. It is concluded that website-based Arabic digital comics can improve the mastery of vocabulary and the ability to read Arabic of grade IV elementary school students. The implication of this research is that website-based Arabic language digital comic media can be used to help students learn.